Consider functions f and g.1 + 12f(1) = 12 + 4. – 12for * # 2 and 7 -64.2 – 16. + 1641 +48for a # -12 Which expression is equal to f(x) · g(t)?OA.41 - 81 + 61OB.SIKIAOC.21 + 6I + 2D.6
![Consider functions f and g1 12f1 12 4 12for 2 and 7 642 16 1641 48for a 12 Which expression is equal to fx gtOA41 81 61OBSIKIAOC21 6I 2D6 class=](https://us-static.z-dn.net/files/dab/6a1a4ec505884b7afcfa7fc30346eadc.png)
Given the following functions below,
[tex]\begin{gathered} f(x)=\frac{x+12}{x^2+4x-12}\text{ and} \\ g(x)=\frac{4x^2-16x+16}{4x+48} \end{gathered}[/tex]Factorising the denominators of both functions,
Factorising the denominator of f(x),
[tex]\begin{gathered} f(x)=\frac{x+12}{x^2+4x-12}=\frac{x+12}{x^2+6x-2x-12}=\frac{x+12}{x(x+6)-2(x+6)}=\frac{x+12}{(x-2)(x+6)} \\ f(x)=\frac{x+12}{(x-2)(x+6)} \end{gathered}[/tex]Factorising the denominator of g(x),
[tex]\begin{gathered} g(x)=\frac{4x^2-16x+16}{4x+48}=\frac{4(x^2-4x+4)}{4(x+12)} \\ \text{Cancel out 4 from both numerator and denominator} \\ g(x)=\frac{x^2-4x+4}{x+12}=\frac{x^2-2x-2x+4}{x+12}=\frac{x(x-2)-2(x-2)}{x+12}=\frac{(x-2)^2}{x+12} \\ g(x)=\frac{(x-2)^2}{x+12} \end{gathered}[/tex]Multiplying both functions,
[tex]undefined[/tex]